Laparoscopic Pancreaticoduodenectomy After Roux-en-Y Gastric Bypass: Case Report and Literature Review - Makai-Popa Silviu-Tiberiu; De Blasi Vito; Moga Marius Alexandru; Arru Luca; Goergen Martine; Azagra Juan Santiago (Case Reports in Surgery)
This is a case report of an alternate laparoscopic reconstruction possibility in a patient that required a cephalic duodenopancreatectomy (DPC) who previously underwent a Roux-en-Y gastric bypass (RYGB). The question of what type of reconstruction is to be performed in such patients is thoroughly debated in this article.